The Influence of Content Strategy on Increasing Engagement on The Instagram Account @lionparcel_solo - Erlina Kusuma DEVI; Gilang Habib Azky PRATAMA (International Journal of Environmental, Sustainability, and Social Science, 2025)
The advancement of digital technology has driven significant changes in communication and marketing strategies, including the use of social media as a primary channel for interaction between companies and their audiences. Instagram has become one of the most effective platforms for fostering closeness and enhancing user engagement. This study aims to examine the influence of content strategy on engagement on the Instagram account @lionparcel_solo, which serves as a promotional and communication medium for courier service offerings. This research employs a quantitative method by distributing questionnaires to 100 respondents who are active followers of the account. The content strategy variable is measured through visual quality, posting consistency, presentation creativity, message relevance, and content interactivity. Meanwhile, engagement is assessed based on likes, comments, shares, saves, views/reach, and direct participation. The analysis results indicate that content strategy has a positive and significant effect on engagement. The coefficient of determination shows that the quality of the implemented content strategy can explain a substantial portion of the variation in engagement. These findings emphasize the importance of consistent, relevant, and appealing content planning and management in increasing audience engagement and supporting the effectiveness of digital marketing communications on the @lionparcel_solo account.